BizPlan Builder : (South-Western College Publishing, 1997)
One of the most important business decisions you need to make begins here. BizPlan Builder is the time-saving solution for anyone who needs to write an effective business plan - from the entrepreneur seeking funding to the corporate manager or team leader introducing a new product or product line. This proven, comprehensive workbook can provide the tools you need to complete a professional, persuasive business plan in minimal time. Comprehensive guidelines, thorough worksheets and sample completed business plans leads you through the thought and writing process for each section of the business plan. With BizPlan Builder's perforated pages, you have an actual rough draft in hand when you finish!